2010
DOI: 10.1021/jm901857d
|View full text |Cite
|
Sign up to set email alerts
|

Thiazole, Oxadiazole, and Carboxamide Derivatives of Artemisinin are Highly Selective and Potent Inhibitors of Toxoplasma gondii

Abstract: We have prepared 23 new dehydroartemisinin (DART) trioxane derivatives (11 thiazoles, 2 oxadiazoles, and 10 carboxamides) and have screened them for in vitro activity in the Toxoplasma lytic cycle. Fifteen (65%) of the derivatives were non-cytotoxic to host cells (TD50 ≥ 320 μM). Eight thiazole derivatives and two carboxamide derivatives displayed effective inhibition of Toxoplasma growth (IC50 = 0.25-0.42 μM), comparable in potency to artemether (IC50 = 0.31 μM) and >100 times more inhibitory than the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…Hence, no MLC could be determined although reduction rates ranged from about 85 to 95% for Hm2, Hm3, Hm4, Hm6 and Hm18. Only a few in vitro studies have tested artemisinin and not its derivatives against protozoa, which were mainly intracellular parasites assessed in cell cultures*for example, Toxoplasma gondii (Nagamune et al, 2007;Hencken et al, 2010) or Neospora caninum (Kim et al, 2002). For evaluation of artemisinin IC 50 values in vitro, two studies used procedures comparable with the present set-up against either Trichomonas vaginalis (Camuzat- Dedenis et al, 2001) or Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, no MLC could be determined although reduction rates ranged from about 85 to 95% for Hm2, Hm3, Hm4, Hm6 and Hm18. Only a few in vitro studies have tested artemisinin and not its derivatives against protozoa, which were mainly intracellular parasites assessed in cell cultures*for example, Toxoplasma gondii (Nagamune et al, 2007;Hencken et al, 2010) or Neospora caninum (Kim et al, 2002). For evaluation of artemisinin IC 50 values in vitro, two studies used procedures comparable with the present set-up against either Trichomonas vaginalis (Camuzat- Dedenis et al, 2001) or Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds were visualized by either exposure of TLC plates to I 2 vapours or by spraying with vanillinsulfuric acid reagent, followed by heating at 110°C for 15 minutes. Si-gel, 60-120 mesh (spectrochem) was used in the column chromatography for the purification of metabolites.The compounds were identified by their spectral IR, ID ( 1 H,13 C, DEPT) and 2D (COSY, HSQC, HMBC) NMR and ESIMS analysis. The purity of all synthesized compounds was determined by HPLC method.…”
mentioning
confidence: 99%
“…The organic layer (ethyl acetate) was dried (Na 2 SO 4 ) and concentrated in vacuo to furnish the crude products. Pure DHA monomers and dimers(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were obtained by column chromatography (silica gel) using hexane-ethyl acetate (8-5:2-5 v/v) as eluent.3-[4'-{1a'-(12aβ-Dihydroxyartemisinoxy)}-ethoxyphenyl]-1-(2", 4"-dimethoxyphenyl)-2-propen-1-one (6): Elution of the column with n-hexane-ethyl acetate (70:20) yielded a viscous compound, 90% (w/w) yield; IR ν max (neat): 1654 (chalcone), 1253, 1169, 1109 (ether), 1601, 1459, 1362, 1026, 984 (aromatics) cm -1 ; 1 H, COSY-NMR (300 MHz, Acetone-d 6 ): δ 0.84 (3H, d, J =9.3 Hz, H 3 -13a), 0.88 (3H, d, J =7.5 Hz, H 3 -14a), 1.21 (3H, s, H 3 -15a), 2.46 (1H, m, H-11a), 3.88, 3.95 (3H each, s, 2 x OCH 3 ), 3.79 (1H, m, Ha-1a'), 4.05 (1H, m, Hb-1a'), 4.27 (2H, d, J=6.3 Hz, H 2 -2a'), 4.78 (1H, d, J=3.0 Hz, αH-12a), 5.42 (1H, s, H-5a), 6.60 (1H, d, J = 2.4 Hz, H-3"), 6.64 (1H, dd, J = 8.7, 2.1 Hz, H-5"), 7.02 (2H, dd, J= 8.7, 1.8 Hz, H-3', H-5'), 7.48 (1H, d, J= 15.9 Hz, H-2), 7.58 (1H, d, J= 15.9 Hz, H-3), 7.64 (1H, m, H-6"), 7.66 (2H, d, J= 8.7 Hz, H-2', H-6'); 13 C, DEPT-NMR (75 MHz, Acetone-d 6 ): δ 12.82 (C-13a), 20.18 (C-14a), 24.64 (C-8a), 25.07 (C-2a), 25.75 (C-15a), 31.29 (C-11a), 34.96 (C-9a), 36.68 (C-3a), 37.57 (C-10a), 44.90 (C-7a), 53.00 (C-1a), 55.51, 55.79 (2 x OCH 3 ), 66.54 (C-1a'), 67.92 (C-2a'), 81.01 (C-6a, q), 87.91 (C-5a), 98.79 (C-3"), 101.99 (C12a), 103.88 (C-4a, q), 106.13 (C-5"), 115.54 (C-5', C-5'), 122.73 (C-1", q), 125.58 (C-2), 128.60 (C-1', q), 130.34 (C-2', C-6'), 132.68 (C-6"), 141.33 (C-3), 160.89 (C-2", q), 161.17…”
mentioning
confidence: 99%
“…The obtained results expressed as IC 50 showed that the tested compounds had almost hundred times higher antitoxoplasmic activity than trimethoprim. Interestingly, two thiazole trioxanes used in the same experiment appeared to be parasiticidal at the concentration of 10 mM after 24 h treatment of intracellular parasites [53]. The examined reversed amidines, designated as DB750 and DB786, also displayed in vitro anti-parasitic action toward both Neospora caninum and T. gondii.…”
Section: Other Synthetic Compoundsmentioning
confidence: 90%